2022
DOI: 10.3168/jds.2022-22177
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Holstein calves and heifers carrying the SLICK1 allele to heat stress in California and Florida dairy farms

Abstract: Inheritance of the SLICK1 allele of the prolactin receptor gene improves thermotolerance of lactating Holstein cows under humid heat stress conditions. The aim of this study was to investigate whether pre-and postweaning Holstein heifers carrying the SLICK1 allele would show physiological responses indicative of higher tolerance to heat stress in high-and low-humidity climates. A total of 101 heifer calves of two age groups heterozygous for the SLICK1 allele and 103 wild-type half-siblings were evaluated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In some experiments during heat stress, slick Holsteins had greater sweating rates than wild-type Holsteins (Dikmen et al, 2008(Dikmen et al, , 2014, whereas no difference was found between genotypes in another experiment (Carmickle et al, 2022). Angus × Senepol heifers inheriting the slick mutation experienced greater transepidermal water loss than wild-type animals (Eisemann et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In some experiments during heat stress, slick Holsteins had greater sweating rates than wild-type Holsteins (Dikmen et al, 2008(Dikmen et al, , 2014, whereas no difference was found between genotypes in another experiment (Carmickle et al, 2022). Angus × Senepol heifers inheriting the slick mutation experienced greater transepidermal water loss than wild-type animals (Eisemann et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…The gene is also frequent in the Senepol breed located on the Caribbean island of St. Croix; presumably, some founder animals possessed the gene. Crossbreeding has also been used to deliberately introduce the SLICK1 mutation into other breeds such as Holstein by crossbreeding (Olson et al, 2003;Dikmen et al, 2008Dikmen et al, , 2014Carmickle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dikmen et al (2014) indicated that rectal temperature, respiration rates and sweating rates were lower in slick cows than wild-type cows. Carmickle et al (2022) reported that the presence of SLICK1 allele of the prolactin receptor gene was associated with low rectal temperature rates in pre and post-weaning Holstein females. Moreover, heat tolerance has a negative genetic correlation with milk production parameters (Aguilar et al, 2009).…”
Section: Selection For Heat Tolerance and Its Importancementioning
confidence: 99%
“…Slick-haired Criollo Limonero non-pregnant heifers had lower rectal temperature and respiratory rates than normal-haired heifers ( Landaeta-Hernández et al, 2021 ). Pre-weaned Holstein calves and growing heifers carrying the SLICK1 allele also maintained lower rectal temperature when exposed to high-humidity heat during summer ( Carmickle et al, 2022 ). Criollo Limonero cattle slick females had larger sweat glands (more consistent with those of B. indicus cattle) compared to wild-type females ( Landaeta-Hernández et al, 2011 ).…”
Section: Gene Editing To Alleviate the Effects Of Heat Stress On Euro...mentioning
confidence: 99%